1998
DOI: 10.1136/adc.78.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Hyporesponsiveness to intradermal administration of hepatitis B vaccine in insulin dependent diabetes mellitus

Abstract: The immune response to intradermal or intramuscular hepatitis B vaccine in 18 children with insulin dependent diabetes mellitus (IDDM) compared with 24 healthy children was studied. Patients were divided into responders, hyporesponders, and non-responders according to their antihepatitis B serum concentrations after hepatitis B vaccination. We also studied HLA class II antigen distribution and did delayed type hypersensitivity (DTH) tests on children with IDDM and controls.No diVerence in the immune response (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…Li Volti et al (38) reported 77.8% seroprotection with intradermal administration compared with 100.0% seroprotection with intramuscular administration. Among children without diabetes, 100.0% in both intradermal and intramuscular arms achieved seroprotection (38). Other studies have found improved results with intradermal administration of the hepatitis B vaccine in dialysis patients (48).…”
Section: Resultsmentioning
confidence: 99%
“…Li Volti et al (38) reported 77.8% seroprotection with intradermal administration compared with 100.0% seroprotection with intramuscular administration. Among children without diabetes, 100.0% in both intradermal and intramuscular arms achieved seroprotection (38). Other studies have found improved results with intradermal administration of the hepatitis B vaccine in dialysis patients (48).…”
Section: Resultsmentioning
confidence: 99%
“…A lower immune response in children with DM type 1 compared to controls was found after intradermal (instead of intramuscular) administration of the hepatitis B vaccine [5]. It has been suggested that this lower response is probably partly the result of an impaired macrophage function in this patient group [5].…”
Section: Defects In Innate Immunitymentioning
confidence: 94%
“…For instance, adaptive humoral immunity in diabetic patients expresses normal levels of serum antibodies and normal response to vaccinations. 18,[51][52][53] In adaptive cellular immunity, the proliferative response of lymphocytes in diabetic patients is inhibited with some stimuli, such as Staphylococcus aureus and phytohemagglutinin, and normal with others. 10 However this alteration does not appear to enhance infection susceptibility in diabetic patients.…”
Section: Immune Deficiencies In a Diabetic Patientmentioning
confidence: 99%